Cognitive flexibility and entrepreneurial creativity: the chain mediating effect of entrepreneurial alertness and entrepreneurial self-efficacy - Yu, Xiaoling; Zhao, Xiuli; Hou, Yongxiong (Frontiers in Psychology, 2023)
Entrepreneurial creativity is an important part of entrepreneurs' competency structure, and studies have been conducted to explore its impact on outcome variables like entrepreneurial performance, etc., but there are fewer studies on its antecedent variables at the individual level. In the relational model of entrepreneurial creativity, cognitive flexibility, entrepreneurial alertness, and entrepreneurial self-efficacy are included to construct a mediated model, and data are collected from a research sample of 325 entrepreneurs for empirical analysis. The results indicate that: cognitive flexibility has a positive effect on entrepreneurial creativity; entrepreneurial alertness plays an independent mediating role between cognitive flexibility and entrepreneurial creativity, which is similar to how entrepreneurial self-efficacy plays the role between cognitive flexibility and creativity; entrepreneurial alertness and entrepreneurial self-efficacy then play a chain mediating role between cognitive flexibility and creativity. These findings reveal that three variables jointly influence entrepreneurial creativity, providing new theoretical and practical insights for understanding and enhancing entrepreneurial creativity. In addition, the study provides valuable guidance for 2 entrepreneurship education and training, which can help entrepreneurs to better utilize their creativity and thus promote innovation and success in entrepreneurial activities.